Humanitarianism a dictionary of concepts - Allen, Tim 1956-; MacDonald, Anna 1981-; Radice, Henry (Routledge, 2018)
"Humanitarian action has in recent years confronted geopolitical challenges that have upended much of its conventional modus operandi and presented threats to its foundational assumptions and legal frameworks. Humanitarianism: A Dictionary of Concepts provides an authoritative analysis that attempts to rethink, rather than merely problematize or define the issues at stake in contemporary humanitarian debates"...